Implanted High Density Cuff Electrodes Functionally Activate Human Tibial and Peroneal Motor Units Without Chronic Detriment to Peripheral Nerve Health. Issue 6 (18th March 2020) - Delianides, Christopher; Tyler, Dustin; Pinault, Gilles; Ansari, Rahila; Triolo, Ronald
Abstract : Objective: Peripheral nerve stimulation via multi‐contact nerve cuff electrodes (NCEs) has proved effective in restoring function to individuals with lower‐extremity paralysis. This study investigates clinical measures of nerve health over one year post‐implantation of a composite flat‐interface nerve electrode (C‐FINE) on the tibial and peroneal nerves above the knee in a human volunteer. This represents the first deployment of a novel NCE on new neural targets in a uniquely challenging location prone to prolonged externally applied forces, making acute and chronic postoperative observation critical. Materials and Methods: A 27‐year‐old man with an incomplete spinal cord injury (AIS C) at the C3 to C4 level received eight‐contact C‐FINEs bilaterally on the tibial and peroneal nerves, proximal to the knee. Access to four contacts per cuff exhibiting the most desirable responses was externalized via temporary percutaneous leads. Percutaneous leads were later removed, with contacts generating the best dorsiflexion (two of four) and plantar flexion (one of four) reconnected to a permanently implanted pulse generator. For 13 months post‐implantation, nerve health and cuff performance were assessed through motor nerve conduction velocity (MNCV) studies, clinical needle electromyography, compound motor action potential (CMAP), sensory nerve action potential (SNAP), stimulation‐evoked tetanic moment collection, and lower‐limb circumference measurements. Results: Tibial and peroneal MNCVs remained stable bilaterally above 40 m/sec, with CMAPs increased or stable after six months. SNAPs remained stable across all measurements. CMAP initial charge thresholds remained below 50 nC, with minimal changes to muscle recruitment order in three of four externalized contacts per cuff. Peak tetanic moments remained stable, with bilateral increases in thigh and calf circumferences of 5% and 14% over one year. Conclusions: Above‐knee tibial and peroneal NCEs can restore stimulated ankle‐joint function without chronic nerve health detriments. Alongside previous femoral nerve data, this study demonstrates the ability of NCEs to enhance lower‐extremity function with limited neuromuscular impact.